2005
DOI: 10.1111/j.0033-3298.2005.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Governance in the UK Public Sector: the Involvement of the Governing Board

Abstract: Governing boards are a prominent feature of many public sector organizations today. These boards have been modelled on the private sector board of directors. Like company boards, one of their main functions is to provide strategic leadership and policy direction for the organization. The role of managers and chief executives is to implement this. This paper examines the extent of involvement of one public sector board, the school governing body, in strategic activity. Using empirical evidence from a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 22 publications
2
54
0
7
Order By: Relevance
“…Specifically, this leads us to hypothesise that: In addition to this, it might be argued that public services undergoing corporatisation will face similar pressures to business units in divisionalised organisations to re-focus 12 management work on more strategic activities. In part this follows from the points made earlier about the shift towards more 'complete' organisations, which replicate private firms in terms of their governance structures, for example, with the creation of executive boards (Cornforth 2003;Farrell 2005). A demand for more resources to be devoted to strategy may also be exaggerated by the need to plan services in a more uncertain, competitive environment, and the enhanced performance demands generated by control from the centre (Bilodeau et al 2007).…”
Section: Technical Perspectivesmentioning
confidence: 99%
“…Specifically, this leads us to hypothesise that: In addition to this, it might be argued that public services undergoing corporatisation will face similar pressures to business units in divisionalised organisations to re-focus 12 management work on more strategic activities. In part this follows from the points made earlier about the shift towards more 'complete' organisations, which replicate private firms in terms of their governance structures, for example, with the creation of executive boards (Cornforth 2003;Farrell 2005). A demand for more resources to be devoted to strategy may also be exaggerated by the need to plan services in a more uncertain, competitive environment, and the enhanced performance demands generated by control from the centre (Bilodeau et al 2007).…”
Section: Technical Perspectivesmentioning
confidence: 99%
“…This lack was further confirmed by different scholars, such as Hodges et al (1996), Cornforth and Edwards (1999) and Farrell (2005), who underline the organisation's board or governing body as a particular object of interest because of the increasing relevance of board control in a very wide range of public sector services and organisations. Thus, as Skelcher (1998) already pointed out, it is expedient to carry out an in-depth analysis of their internal and external functioning.…”
Section: Introductionmentioning
confidence: 94%
“…Dean et al (2007) reported that, perhaps unsurprisingly, governing bodies in the cases in their study felt happier supporting rather than challenging. Farrell (2005), in a small-scale study, reported that governors rarely challenged the headteacher or changed headteachers' decisions. These findings are supported by the national survey of governors by Balarin et al (2008), which showed that governors ranked supporting the headteacher as top of list of 10 governing activities undertaken in the previous year and challenging the headteacher eighth.…”
Section: Governing Body Processes and Rolesmentioning
confidence: 99%
“…These findings are supported by the national survey of governors by Balarin et al (2008), which showed that governors ranked supporting the headteacher as top of list of 10 governing activities undertaken in the previous year and challenging the headteacher eighth. Farrell (2005) also asserted that, while policies have empowered governors to take up a strategic role, the regulations issued over the years hinder governors' involvement in strategy. This view echoes that of Earley (2003).…”
Section: Governing Body Processes and Rolesmentioning
confidence: 99%